Pengaruh Kesulitan Belajar Terhadap Prestasi Belajar Siswa dalam Mata Pelajaran Produktif Akuntansi (Standar Kompetensi : Mengelola Dana Kas Kecil) di Kelas X Administrasi Perkantoran SMK Pasundan 1 Bandung - Mitha Octavyan (LPPM Bunga Bangsa Cirebon, 2019)
The purpose of this research is to know the imagine of student’s learning disability and student’s learning achievement in Accountancy Productive lesson in X class of Adm. Office in SMK 1 Pasundan Bandung and also to know the effect of learning disability for their learning achievement in Accountancy Productive lesson in X class Adm. Office of SMK 1 Pasundan Bandung. The method that used in this research is explanation survey method, and the population is the students of X class Adm. Office of SMK 1 Pasundan Bandung, with the amount of sample that used is counted 123 students of population counted 178 students. The technique that used in sample taking use simple random sampling. The student’s learning disability data is acquired from spreading of questionnaire, while student’s learning achievement data is acquired by document studying. The result of research shows that learning disability has a negative influential about student’s learning achievement in Accountancy Productive lesson in X class Adm. Office of SMK 1 Pasundan Bandung. The influence which are given by learning disability about student’s learning achievement is about 82,5%. The imagine of student’s learning disability is in the high category with the percentage is 53,66% and student’s learning achievement is in the low category with the percentage is 43,09%. The implication from this research is student who experience the difficulty of learning will experience the trouble in next learning process, so that in the end the student will left away behind in his learning process.. Abstrak Penelitian ini bertujuan untuk mengetahui gambaran kesulitan belajar siswa dan prestasi belajar siswa dalam mata pelajaran produktif Akuntansi di kelas X Adm. Perkantoran SMK Pasundan 1 Bandung serta untuk mengetahui pengaruh kesulitan belajar terhadap prestasi belajar siswa dalam mata pelajaran produktif Akuntansi di kelas X Adm. Perkantoran SMK Pasundan 1 Bandung. Metode yang digunakan dalam penelitian ini adalah metode survei eksplanasi, yang menjadi populasi adalah siswa kelas X Adm. Perkantoran di SMK Pasundan 1 Bandung, dengan jumlah sampel yang digunakan sebanyak 123 orang siswa dari populasi sebanyak 178 orang. Teknik yang digunakan dalam pengambilan sampel menggunakan simple random sampling. Data kesulitan belajar siswa diperoleh dari penyebaran angket, sedangkan data prestasi belajar siswa diperoleh dari telaah dokumen. Hasil penelitian menunjukkan bahwa kesulitan belajar berpengaruh negatif terhadap prestasi belajar siswa dalam mata pelajaran produktif Akuntansi di kelas X Adm. Perkantoran SMK Pasundan 1 Bandung. Pengaruh yang diberikan kesulitan belajar terhadap prestasi belajar siswa adalah sebanyak 82,5%. Gambaran kesulitan belajar siswa berada pada kategori tinggi dengan presentase 53,66% dan prestasi belajar siswa berada dalam kategori rendah dengan presentase 43,09%. Implikasi dari hasil penelitian ini adalah siswa yang mengalami kesulitan belajar akan mengalami hambatan dalam proses belajar berikutnya, yang pada akhirnya siswa tersebut akan mengalami ketertinggalan dalam proses belajarnya